1987
DOI: 10.1111/j.1600-0765.1987.tb01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraoral control of geometry for digital subtraction radiography

Abstract: The use of a cephalostat to stabilize projection geometry for subtraction radiography was investigated. Six replicate repositionings of patients within a cephalostat indicated that the mean angular disparity between repositioning was 0.33 ± 0.10 degrees. Subtraction images produced from films of a phantom with artificial periodontal defects exposed using the cephalostat or stent technique were compared. There was no significant difference in the standard deviations of the gray level histograms obtained using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
6

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(73 citation statements)
references
References 14 publications
(10 reference statements)
0
67
0
6
Order By: Relevance
“…Ideally, this will allow assessment in terms of quality and amount of bone, location of anatomical structures, and longitudinal morphological change through bone loss along the implant surface. Digital subtraction radiography was introduced into the field of periodontal research in the 1980s as one of the most versatile approaches to assessment of longitudinal bone change 8,10,11,28) . Jeffcoat et al 12) used a reference wedge calibrated to different thicknesses, which was incorporated into the periapical radiograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, this will allow assessment in terms of quality and amount of bone, location of anatomical structures, and longitudinal morphological change through bone loss along the implant surface. Digital subtraction radiography was introduced into the field of periodontal research in the 1980s as one of the most versatile approaches to assessment of longitudinal bone change 8,10,11,28) . Jeffcoat et al 12) used a reference wedge calibrated to different thicknesses, which was incorporated into the periapical radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the implant fixture itself acts as its own ruler to compensate for linear measurement of bone loss. Although digital subtraction technique 8,11,12,27,28) with PE radiographs has recently become widely used for bone loss assessment, and most dentists in private clinics routinely use PE radiographs for implant site assessment, no studies have reported the accuracy of linear measurement of implant length based on PE radiographs compared with that on other radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques have recently been developed for determining the degree of angulation error that occurs with each radiograph in a longitudinal series . Methods have also been developed for using cephalostats to control projection geometry (Jeffcoat et al, 1987). In sum, various methods have been developed for controlling projection geometry.…”
Section: Control Of Exposure Geometrymentioning
confidence: 99%
“…[12][13][14][15][16][17] The various reports all can be applied to study radiographic changes at the implantation site as a function of time post-treatment, but do not allow for comparison of radiographic and clinical data as no application is available for such comparative studies. The main improvement of the method introduced in this study is that it makes such comparative studies possible.…”
Section: Measuring Errors (Mm Mean ± ± Sd) As Calculated For Each Sementioning
confidence: 99%